Biodiversity in mountain soils above the treeline - Praeg, Nadine; Steinwandter, Michael; Urbach, Davnah; Snethlage, Mark A; Alves, Rodrigo P; Apple, Martha E; Bilovitz, Peter; Britton, Andrea J; Bruni, Estelle P; Chen, Ting-Wen; Dumack, Kenneth; Fernandez-Mendoza, Fernando; et al. (Biological reviews of the Cambridge Philosophical Society, 2025)
Biological diversity in mountain ecosystems has been increasingly studied over the last decade. This is also the case for mountain soils, but no study to date has provided an overall synthesis of the current state of knowledge. Here we fill this gap with a first global analysis of published research on cryptogams, microorganisms, and fauna in mountain soils above the treeline, and a structured synthesis of current knowledge. Based on a corpus of almost 1400 publications and the expertise of 37 mountain soil scientists worldwide, we summarise what is known about the diversity and distribution patterns of each of these organismal groups, specifically along elevation, and provide an overview of available knowledge on the drivers explaining these patterns and their changes. In particular, we document an elevation-dependent decrease in faunal diversity above the treeline, while for cryptogams there is an initial increase above the treeline, followed by a decrease towards the nival belt. Thus, our data confirm the key role that elevation plays in shaping the biodiversity and distribution of these organisms in mountain soils. The response of prokaryote diversity to elevation, in turn, was more diverse, whereas fungal diversity appeared to be substantially influenced by plants. As far as available, we describe key characteristics, adaptations, and functions of mountain soil species, and despite a lack of ecological information about the uncultivated majority of prokaryotes, fungi, and protists, we illustrate the remarkable and unique diversity of life forms and life histories encountered in alpine mountain soils. By applying rule- as well as pattern-based literature-mining approaches and semi-quantitative analyses, we identified hotspots of mountain soil research in the European Alps and Central Asia and revealed significant gaps in taxonomic coverage, particularly among biocrusts, soil protists, and soil fauna. We further report thematic priorities for research on mountain soil biodiversity above the treeline and identify unanswered research questions. Building upon the outcomes of this synthesis, we conclude with a set of research opportunities for mountain soil biodiversity research worldwide. Soils in mountain ecosystems above the treeline fulfil critical functions and make essential contributions to life on land. Accordingly, seizing these opportunities and closing knowledge gaps appears crucial to enable science-based decision making in mountain regions and formulating laws and guidelines in support of mountain soil biodiversity conservation targets.
Keywords: biogeography; Altitude; bacteria; biodiverzita; Soil; Soil Microbiology; alpine soils; nadmořská výška; systematic mapping; cryptogams; Bacteria; protists; půda; invertebrates; fungi; microbial diversity; půdní mikrobiologie; Animals; lichens; zvířata; Biodiversity